2015
DOI: 10.1002/ajmg.a.36856
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of genotype‐phenotype correlation in 18 patients carrying a 1q24q25 deletion

Abstract: Interstitial deletion 1q24q25 is a rare rearrangement associated with intellectual disability, growth retardation, abnormal extremities and facial dysmorphism. In this study, we describe the largest series reported to date, including 18 patients (4M/14F) aged from 2 days to 67 years and comprising two familial cases. The patients presented with a characteristic phenotype including mild to moderate intellectual disability (100%), intrauterine (92%) and postnatal (94%) growth retardation, microcephaly (77%), sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 34 publications
6
61
1
Order By: Relevance
“…Since then, pangenomic approaches such as CMA permit to better characterisation of the 1q proximal region and refinement of genotype–phenotype correlations. In 2015, Chatron et al 20 reported that the large proximal subregion 1q23.3q24.1 could be strongly associated with an increased risk of renal and cardiac abnormalities in a cohort of 18 patients 20. In our study, we present eight patients carrying an 1q23.3q24.1 deletion that encompass the PBX1 gene.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Since then, pangenomic approaches such as CMA permit to better characterisation of the 1q proximal region and refinement of genotype–phenotype correlations. In 2015, Chatron et al 20 reported that the large proximal subregion 1q23.3q24.1 could be strongly associated with an increased risk of renal and cardiac abnormalities in a cohort of 18 patients 20. In our study, we present eight patients carrying an 1q23.3q24.1 deletion that encompass the PBX1 gene.…”
Section: Discussionmentioning
confidence: 70%
“…Among the two patients reported by Chatron et al who exhibited no CAKUT, one patient (PT1) had a deletion with an uncertain proximal breakpoint which did not permit prediction of whether the PBX1 gene is included in the deletion. The other patient (patient 7) was only 1 year old and may not yet have renal manifestations 20. Two other cases reported in DECIPHER harbour a PBX1 deletion (ID 276516 and 252430) but no information about their uronephrologic condition was available.…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal features reported include prenatal onset growth retardation, which persists as significant postnatal short stature of up to ‐5SD, microcephaly up to ‐4SD, small hands and feet with brachydactyly and in particular, fifth finger clinobrachydactyly. Of those investigated, several also had delayed bone age (Chatron et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reported dysmorphic facial features include micrognathia, small, low set ears with absent or hypoplastic lobes, a short nose with a broad bridge and bulbous tip, full eye lids or partial ptosis, a tented upper lip and a small chin. A few patients have been reported to have a broad neck, hypertelorism, a cleft lip/palate or high palate (Burkardt et al, ; Chatron et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples -just on the long arm of chromosome 1-include 1q43q44 microdeletions, 55,56 1q41q42 microdeletions, 57-59 and 1q24q25 microdeletions. 60,61 Further insight into microdeletion/microduplication syndromes comes by limiting comparisons of CNVs to just those with a phenotype of interest. For example, with 1q43q44 microdeletions, microcephaly, agenesis of the corpus callosum, and seizures appear to be caused by different SROs/genes.…”
Section: Discovery Of Microdeletion and Microduplication Syndromesmentioning
confidence: 99%